The aftermath of the Merck's HIV vaccine trial - Iaccino, Enrico (BioMed Central, 2008)
The recently released results of the Merck's Phase IIb "test-of concept" vaccine trials have shown no protection from HIV-1 infection in the vaccinated group compared with a control group vaccinated with placebo. The study was designed to test the Merck's MRKAd5 trivalent candidate vaccine. The vaccine formulation was expected to stimulate a HIV-specific T cell immune response and to either prevent infection, or to reduce the levels of the viral load in vaccinated subjects. Upon the first evaluation of the interim data, the independent Data and Safety Monitoring Board (DSMB) underscored no protection from HIV-1 infection in the vaccine-inoculated volunteers compared with the control group; accordingly, the vaccine trial was stopped. This disappointing outcome warrants a critical analysis of the current vaccine studies and calls for a renewed effort toward a rational design of novel immunogens to be tested in large primate trials.